LINKING SELF EFFICACY AND WORK ENGAGEMENT TO EMPLOYEE PERFORMANCE: THE INTERVENING ROLE OF WORK MOTIVATION - Setiani, Setiani; Khotimah, Ayu Husnul (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 8 No 1 (2022): The 8th International Conference Of Islamic Economics And Business (ICONIES 2022), 2022)
This study aims to determine the influence of self-efficacy, work engagement, and work motivation on employee performance and the role of work motivation in mediating self-efficacy and work engagement. This study uses a quantitative approach. The research population is employees of P.T. Aji Vasthu Construction, and the sample is 98 respondents with a saturated sampling technique. Data collection techniques by observation and questionnaires. The data analysis method used a validity test, reliability test, normality test, linearity test, path analysis, and Sobel test with the help of SPSS 20.0 software for Windows. The results showed that self-efficacy significantly affected employee performance, and work engagement did not affect employee performance. The work motivation could not mediate the relationship between self-efficacy and work engagement on employee performance. Work motivation cannot judge the impact of work engagement on employee performance, and work motivation has a positive and significant direct effect on employee performance. These findings offer practical implications for organizational leaders to improve employee performance by stimulating self-efficacy to grow and develop within employees. Several ways can be done by adding insight and experience, digging for information, and a conducive environment.